Researching a Risky Business? The Use of Freedom of Information to Explore Counterterrorism Security at Museums in the United Kingdom. (2nd January 2022) - Atkinson, Colin; Yates, Donna; Brooke, Nick
Abstract: This article reflects on the value and limitations of the use of Freedom of Information (FOI) in the collection of data on counterterrorism policies and practices at museums in the United Kingdom (UK). In doing so, this article re-interprets the museum within the "single narrative" of global jihadist terrorism before using FOI to uncover counterterrorism security measures at museums in the UK. We particularly signpost the importance of the role of the museum security manager as the interface between the museum and the wider UK counterterrorism network. Throughout, but particularly in the discussion section, the article reflects on the value and limitations of FOI as a social research tool. The conclusion highlights the requirement for further qualitative enquiry into the museum as an emerging site of counterterrorism security discourse and practice, particularly in relation to how museum security managers understand and navigate this unique cultural space.